ANALISIS PEMANFAATAN SUMBER BELAJAR OLEH GURU GEOGRAFI DI SMA NEGERI 1 BASO KABUPATEN AGAM - NURHAYATI, NURHAYATI; Rahmanelli, Rahmanelli (DEPARTEMEN GEOGRAFI FIS UNP, 2024)
This study discusses the use of learning resources by geography teachers at SMA Negeri 1 Baso Kabupaten Agam. The purpose of the study was to analyze the availability of learning resources, learning resources used by geography teachers in the learning process, and the creativity of geography teachers in utilizing learning resources at SMA Negeri 1 Baso Kabupaten Agam. This type of research is descriptive qualitative. The informants in the study were three geography teachers, the principal, and representatives of infrastructure as providers of learning resources at SMA Negeri 1 Baso, Agam Regency, as well as three students, namely representatives from class X, XI, and XII. Data collection techniques used are through observation, interviews and documentation. Data analysis techniques include data collection, data reduction, data presentation/, and drawing conclusions. The results of this study found that; 1) The availability of learning resources used by geography teachers at SMA Negeri 1 Baso Kabupaten Agam is generally quite available 2) Learning resources used by teachers in learning are learning resources that are already available in schools. Teachers often use learning resources such as teachers as the main learning resource, library books and some teaching materials from the internet. 3) The creativity of geography teachers in utilizing learning resources is still lacking, teachers rarely process and use varied types of learning resources in the learning process. Keywords: learning resources, learning, teacher creativity